2021
DOI: 10.1021/acs.est.1c03618
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microplastic Concentrations in Five Megacities of Northern and Southeast China

Abstract: Airborne microplastics (MPs) are receiving increasing attention due to their ubiquitous nature and the potential human health consequences resulting from inhalation. The limited data for airborne MP concentrations vary widely among studies (∼4 orders of magnitude), but comparisons are tenuous due to the inconsistent collection and detection/enumeration methodologies among studies. Herein, we used uniform methodologies to obtain comparable airborne MP concentration data to assess MP exposure intensity in five C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
0
36
1
Order By: Relevance
“…7 Today, more MPs have been found in indoor rather than outdoor environments. 7 Although the concentrations 10 and deposition rates 18,19 are often used to characterize airborne MPs, the size and density of MPs would influence its deposition on the respiratory system, with smaller, less dense particles reaching deeper parts of the lungs. 20,21 Recently, the presence of 33 MPs in 13 human lung tissues was first reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Today, more MPs have been found in indoor rather than outdoor environments. 7 Although the concentrations 10 and deposition rates 18,19 are often used to characterize airborne MPs, the size and density of MPs would influence its deposition on the respiratory system, with smaller, less dense particles reaching deeper parts of the lungs. 20,21 Recently, the presence of 33 MPs in 13 human lung tissues was first reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The same sampling and detection method was used to assess the intensity of exposure to MPs in the atmosphere of ve megacities in China. 72 The results showed that the concentrations of MPs in the air in northern cities (358 AE 132 items per m 3 ) were higher than those in southeast cities (230 AE 94 items per m 3 ). Signicant differences in the distribution of atmospheric MPs in different functional areas of the same city show that the above guesses are wellfounded.…”
Section: Morphological Characteristics Of Atmospheric Mpsmentioning
confidence: 90%
“…The main source of airborne MPs is synthetic bers. 72,73 Globally, more than 90 million tons of textile bers were produced in 2016. Two-thirds of them were synthetic and plastic bers, and the production rate has grown at around 6.6% per year over the past decade.…”
Section: Morphological Characteristics Of Atmospheric Mpsmentioning
confidence: 99%
“…Atmospheric M/NPs have aroused substantial concerns in recent years because they can be quickly transported over long distances by wind. Airborne plastics mainly originate from synthetic clothing, synthetic fibers in building materials, plastic waste incineration and road dust [73]. Researchers have found atmospheric M/NPs both indoors and outdoors [74].…”
Section: Airmentioning
confidence: 99%